Levinas, Adorno, and the ethics of the material other - Nelson, Eric Sean (Suny series in contemporary French thought, 2020)
"This book sets up a dialogue between Emmanuel Levinas and Theodor W. Adorno, using their thought to address today's environmental and social-political situation. The chapters focus on critical natural history and the environmental crisis (part 1), religion, prophecy, and the good (part 2), and an asymmetrical account of equality, liberty, and solidarity (part 3). Eric S. Nelson presents a critical ethics of the material other, addressing the alterities, non-identities, and the good that constitute, interrupt, and reorient ethical and social-political forms of life. This ethics of the material other has significant implications. First, the self is constituted through material and communicative relations to others in "other-constitution" rather than individual or collective self-constitution. Second, encounters with the prophetic "other-power" or transcendence of the good in others-in the ordinary mundanities and sufferings of immanent material life-disturb the economies of the individual ego relishing its own happiness and collective identities that codify themselves through the subjugation and refusal of non-human and human others. Finally, the infinite ethical and social-political demand of others calls for unrestricted solidarities that can transform ethical and social-political sensibilities, if always in relation to the material and communicative conditions of contemporary global capitalism"--